Planning the reassignment of frequencies in fiber-wireless access networks - Correia, N. (2017)
FiWi architectures have been proposed as efficient solutions to provide high bandwidth and ubiquity at access network areas. In multi-radio and multi-channel FiWi scenarios an effective frequency assignment should be done to radios so that higher throughput and low delay can be obtained and the best of such architectures is achieved. However, traffic conditions change over time meaning that radio channel reconfigurations can be done to improve network performance. In this article a methodology for FiWi frequency reassignment planning is proposed, together with two algorithms, that avoids service disruption and attempts to increase throughput, reduce delay and increase the overall QoS perceived by users. Results show that the RBR algorithm is the one able to better exploit channel reconfigurations, increasing parallel transmissions and reducing time division required by nodes at the transmission area of each other.